Technology education at the beginning and during school reform in Slovakia - BÁNESZ, Gabriel (Journal of Education, Technology and Computer Science, 2013)
The article presents the aims and objectives of the KEGA project: Analysis of the reform’s impact on technology education in elementary schools. In the contribution, the author presents results of research, which focused on surveys of the state of technology education in elementary schools at the time of the school reform’s introduction. These results will form the basis for comparison of the state of technology education at the beginning of the reform and now.